الاستعمار الغربي و مدى تأثيره في الأدباء والمفكرين والثقافة الإسلامية - Yaacob, Adli (الكلية دار العلوم بجامعة ألمانيا, 2014)
This article discusses about some Muslim literary figures were and still under the influence of the West. During the colonial periods, through education and cu ltural encounters, a new generation of locals who were imbued with Western orientation emerged. The newly westernized locals later occupied significant positions the society and government. On the other hand, there were also a handful of Muslims who went t o the West and studied but remained comfortable with their own culture and were hardly westernized. They remained Islamic and were moderate. Upon their return, they benefitted their people and society .